The Effect of Perceived Organizational Support and Psychological Capital on Job Satisfaction and Knowledge Sharing - Mustika, Silvia Indra; Rahardjo, Kusdi; Prasetya, Arik (UI Scholars Hub, 2020)
In keeping with the ever-growing knowledge-based economy, the role of knowledge itself becomes more significant and it hinges on the management ability to stimulate their organization’s environment to create and nourish knowledge sharing behavior. This research is aimed at determining the effect of perceived organizational support and psychological capital on job satisfaction and knowledge sharing. Drawing from social exchange theory, employee’s knowledge sharing behaviour and satisfaction are the consequences of organizational role-fulfilment. Explanatory research with quantitative approach is used in this research. The primary data was collected using a questionnaire. The sampling method used was a proportional random sampling which provided a sample of 121 non-medical staff at Lavalette Malang Hospital. The data was analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM). The result of this study shows that perceived organizational support is a significant predictor of non-medical staff’s psychological capital and job satisfaction. However, perceived organization support is an insignificant predictor of knowledge sharing. Psychological capital is a significant predictor to both job satisfaction and knowledge sharing, and is successfully mediating the relationship between perceived organizational support and knowledge sharing